Distorsi Pasar Dalam Proses Transaksi Sekuritas Syariah di Pasar Sekunder - Gusniarti Gusniarti (Faculty of Economic and Business, 2015)
Market Distortion on Securties Transaction Process in Secondary MarketMarket distortion is aaberration which causes an imbalance and injustice on the market to be avoided. This study aims to learn more about other forms of distortions such as tadlis, gharar, maysir, ihtikar and bay 'najasy and to recognize its form at the process of transaction in the Islamic capital market, especially the secondary market so that the process securities transactions sharia truly reflects the activity of sharia economic transactions which has values of brotherhood, mutual interest, morality, the orientation of the hereafter and no exploitation. The approach taken is the approach of Jurisprudence and Islamic economics. Results of this study will deepen understanding and clarify the forms of distortion at the transactions in the secondary market so that it can be avoided as much as possible where the transaction finally truly reflect Islamic sharia securities transactions in the capital market.DOI: 10.15408/etk.v14i2.2269